PSYCHOLOGICAL RESILIENCE OF SERVICEMEN DURING COMBAT MISSIONS (Psychology Travelogs, 2023)
The article deals with theoretical aspects of the development of psychological resilience of servicemen in the performance of combat missions.The author of the article defines the concepts of «resilience» and «psychological resilience». The concept of «resilience» is considered in the article as the ability of a person to restore positive mental states. And «psychological resilience» is defined as the ability to ensure the person's resistance to frustration and stressful effects of difficult situations.The article theoretically substantiates approaches to the definition of psychological resilience of servicemen as their ability to adapt, recover and act in situations of risk, challenges, danger, difficulties and adversity. It is noted that the resilience of servicemen is not a static state, but a flexible process that involves the interaction between their life experience and the current life situation.The author of the article investigates the stressors of professional activity of military personnel that affect their psychological resilience. The stressors of servicemen's professional activity are: subjective (individual), which are related to the characteristics of the soldier, his/her age, life values, beliefs, methods and mechanisms of psychological protection, attitude to service activities, interpersonal interaction in the team, family members; objective (situational), which are related to official duties.The article identifies and describes in detail the main aspects of the development of psychological resilience of servicemen in the performance of combat missions. The main aspects of the development of psychological resilience of servicemen are: physiological training, consideration of gender differences in resilience, contribution of training to resilience, formation of thermal resistance.The author of the article concludes that psychological resilience is important not only for the mental but also for the physical health of a serviceman. It is manifested in the cognitive resources that allow for effective problem-solving; emotional skills to withstand stress; social and family factors; the ability to find the purpose and meaning of one's service; and physical resilience to prolonged hardship.
Keywords: resilience; psychological resilience; military personnel; combat missions; professional stressors